Gambia publications in the Science Citation Index Expanded: bibliometrics of institutions and subjects - Bah, Karamo (2019)
Gambia is the smallest country in West Africa and it has contributed to the academic world over the past decades. This study characterized document type, language, publication trend, subject category, international collaboration of Gambia publications during 1900-2016 based on Science Citation Index Expanded in Web of Science. Results showed that Gambia is highly reliant on foreign and international collaboration in research, especially with the UK and the USA. International collaboration was responsible for the increasing scientific production and scientific impact of Gambia over the years. Medical Research Council (MRC) contributed the most Gambia publications, and played an important role in conducting international collaboration. Most of Gambia publications focused on tropical medicine, environmental and occupational public health, immunology and infectious diseases. Gambia has attracted increasing attention from the academic world, with improving scientific production and scientific impact, signaling more prestige in the scientific community. With the information and insights provided in this paper, we managed to obtain a quick overview of Gambia publications that can help make strategic decisions for researchers and governors of scientific research.